Productivity and economics Of rice (Oryza sativa)- based crop sequences under mid- to high-altitude temperate zone of Jammu and Kashmir - BADRUL HASAN (Indian Journal of Agronomy, 2001)
A field experiment was conducted during 1987-92 on a silty clay-loam soil to identify appropriate rice (Oryza sativa L.) - based cropping systems with high produc- tivity in mid- to high-altitude temperate zone of Kashmir Valley. Rice, as a base crop, was sequenced with other feasible crops, viz. rapeseed, wheat (Triticum aestivum L. emend. Fiori & Paol.), lentil (Lens ccflinaris Medikus), oat (Avena sativa L.) and ber- seem (Trifolium alexandrinum L.). A rice-fallow rotation was also included to repre- sent area where soil is unfit due to waterlogging during winter season. Rice-rape- seed sequence recorded sustainable rice yield on a long-term basis. Rice-wheat sequence secured the highest rice yield equivaient (RYE), net returns and energy outputlha, which was followed by rice-rapeseed sequence. Oat had an adverse im- pact on rice yield sustainability as it decreased the same by 24%.